2015
DOI: 10.3354/dao02819
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic characterization reveals the presence of novel fish-associated Chryseobacterium spp. in the Great Lakes of North America

Abstract: Recent reports suggest an emergence of novel Chryseobacterium spp. associated with aquaculture-reared fish worldwide. Herein, we report on multiple Chryseobacterium spp. infecting Great Lakes fishes that are highly similar to previously detected isolates from Europe, Africa, and Asia but have never before been reported in North America. Polyphasic characterization, which included extensive physiological, morphological, and biochemical analyses, fatty acid profiling, and phylogenetic analyses based upon partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…However, in a similar fashion to the eggs and ovarian fluid, on only two occasions were non-F. psychrophilum, non-F. columnare flavobacteria from the same taxon recovered from multiple organs in the same fish (Table 2). Nevertheless, their ability to colonize the splenic, renal, and neurological tissues agrees with experimental challenge data for other newly characterized fish-associated flavobacteria (Loch and Faisal, 2014, 2015b, 2016 and reinforces their infectious potential to feral Oncorhynchus spp. An important finding of this study was that the gameteassociated flavobacteria belonging to four different taxa (e.g., F. columnare and three Chryseobacterium spp.…”
Section: Discussionsupporting
confidence: 73%
“…However, in a similar fashion to the eggs and ovarian fluid, on only two occasions were non-F. psychrophilum, non-F. columnare flavobacteria from the same taxon recovered from multiple organs in the same fish (Table 2). Nevertheless, their ability to colonize the splenic, renal, and neurological tissues agrees with experimental challenge data for other newly characterized fish-associated flavobacteria (Loch and Faisal, 2014, 2015b, 2016 and reinforces their infectious potential to feral Oncorhynchus spp. An important finding of this study was that the gameteassociated flavobacteria belonging to four different taxa (e.g., F. columnare and three Chryseobacterium spp.…”
Section: Discussionsupporting
confidence: 73%
“…The milt and spleen isolates (462 and 435) recovered from the same Chinook Salmon fell into a cluster with C. piscium and C. balustinum (Figure 1), the percent of 16S rRNA gene similarity suggesting that the isolates were more similar to the former (99.7%) than the latter (98.5-98.7%). Indeed, we have previously noted the apparent heterogeneity within the 16S rRNA gene for C. piscium and C. piscium-like isolates (Loch and Faisal 2015b), and results from this study further support this notion. Chryseobacterium sp.…”
Section: Resultssupporting
confidence: 82%
“…In addition to those species that have long been recognized as fish pathogens (e.g., F. columnare, F. psychrophilum, F. branchiophilum, and C. scophthalmum), recent studies have revealed that numerous novel Flavobacterium and Chryseobacterium spp. also cause systemic infections and disease outbreaks in farmed salmonids (reviewed in Loch and Faisal 2015a), including those of the Great Lakes (Loch and Faisal 2014;Loch and Faisal 2015b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…isolated from fish were not able to induce any clinical signs or gross pathological changes in white sturgeon [ 47 ], diverging from what was previously observed in other fish species with other Chryseobacterium sp. strains [ 48 ]. In addition, Citrobacter freundii has been previously isolated from the internal organs of diseased sturgeons, but no detailed description has been reported regarding these infections [ 42 ].…”
Section: Discussionmentioning
confidence: 99%